Selective synthesis of WO3 and W18O49 nanostructures: ligand-free pH-dependent morphology-controlled self-assembly of hierarchical architectures from 1D nanostructure and sunlight-driven photocatalytic degradation - Shirke, Yogita Manikrao; Mukherjee, Shatabdi Porel (CrystEngComm, 2017)
In this study, simple inorganic routes for the synthesis of WO3 and W18O49 nanostructures with variable size and self-assembly are reported. The morphologies and formation of stoichiometric WO3 as well as substoichiometric W18O49 single-crystal phase could be controlled by changing the pH of the reactions medium. This synthesis strategy has the advantages that it is one step, aqueous medium-based, and requires no surfactant or stabilizing agent. Furthermore, it also enables the self-assembly of 1D nanorods of WO3 and W18O49 into hierarchical nanostructures as nanorods bundles, cocoons, urchins, fishbones, etc. This synthesis method may open up a new way to control and tune the stoichiometric and substoichiometric composition of metal oxide nanostructures. Efficient sunlight-driven photocatalytic performance to degrade Rhodamine B (100 mL; 40 mg L-1.) with these tungsten oxide nanostructures was also demonstrated.

Size-controlled cobalt ferrite nanocrystals: magnetically separable reusable nanocatalysts for selective oxidation of styrene - Jeyavani, Vijayakrishnan; Pawar, Sayali; Dadwal, Arun; Joy, Pattayil Alias; Mukherjee, Shatabdi Porel (ChemistrySelect, 2019)
Superparamagnetic cobalt ferrite (CFO) nanocrystals (NCs) with sizes similar to 6 nm and similar to 4 nm were synthesized using a facile solvothermal method using fatty acids, lauric acid and stearic acid, as the capping agents. The synthesized nanocrystals were well characterized by XRD, FT-IR, XPS, SEM and TEM. The formation mechanism was explored and it was shown that the fatty acid was actually chemisorbed as a carboxylate onto the surface of CFO NCs. The experimental results specify that the size and size distribution of the CFO NCs were highly dependent on the length of fatty acid hydrophobic chain. Corresponding changes of the magnetic properties were investigated by measuring magnetization as a function of field and temperature, which suggest that the CFO NCs were superparamagnetic in nature. The catalytic properties for the oxidation of styrene in organic medium were examined by using the synthesized CFO NCs with sizes similar to 6 nm and similar to 4 nm. The synthesized CFO NCs, well dispersible in organic media, were demonstrated to be highly catalytically active, reached 100% conversion of styrene in 12 h with similar to 77% and similar to 82% selectivity for styrene oxide respectively. The magnetic CFO nanocatalysts were easily separated and recovered from the reaction medium by an external magnet, and reused for several cycles without losing catalytic selectivity for styrene oxide.
Keywords: Cobalt ferrite; epoxidation; Fatty acids; magnetic properties; nanocrystals

Scalable mechanochemical synthesis of beta-ketoenamine-linked covalent organic frameworks for methane storage - Asokan, Kiran; Patil, Manoj Krishnat; Mukherjee, Shatabdi Porel; Sukumaran, Santhosh Babu; Nandakumar, T. (Chemistry-An Asian Journal, 2022)
In the current scenario of increased pollution and releasing toxic gases by burning petroleum products, switching to natural gas is more promising for reducing CO2 emissions and air pollutants. Hence, research on Liquefied Natural Gas and Compressed Natural Gas is gaining more value. However, natural gas primarily consists of CH4, which has less energy density than conventional fuels. Interestingly, since the C-H ratio of CH4 gas is 1 : 4, it is easily combustible, gives less carbon footprint, and reduces unburnt hydrocarbon pollution. Hence, research on storing and transporting CH4 has utmost importance, and porous materials are one of the suitable candidates for storing CH4. Herein we report the scalable synthesis of highly porous and crystalline covalent organic frameworks for storing CH4 at room temperature and pressure. Two COFs, namely, Tp-Azo and Tp-Azo-BD(Me)(2), synthesized in 1 kg at similar to 45 g batch scale using a Planetary mixer, displayed a maximum BET surface area of around 3345 m(2)/g, and 2342 m(2)/g and CH4 storage of 174.10 cc/cc and 151 cc/cc, respectively. A comparison of the CH4 sorption of Tp-Azo and Tp-Azo-BD(Me)(2) COFs synthesized in different batches has a variation of only +/- 5 cc/cc and shows the consistency in bulk scale synthesis of COFs. The cyclic equilibrium CH4 adsorption studies showed the COFs are stable with consistent CH4 adsorption and desorption cycles. The present study is a step towards the scalable mechanochemical synthesis of COFs for gas storage applications.
Keywords: CH4 storage; COF; porous material; scalable synthesis